-x-4(7-2x)=4

Simple and best practice solution for -x-4(7-2x)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x-4(7-2x)=4 equation:



-x-4(7-2x)=4
We move all terms to the left:
-x-4(7-2x)-(4)=0
We add all the numbers together, and all the variables
-x-4(-2x+7)-4=0
We add all the numbers together, and all the variables
-1x-4(-2x+7)-4=0
We multiply parentheses
-1x+8x-28-4=0
We add all the numbers together, and all the variables
7x-32=0
We move all terms containing x to the left, all other terms to the right
7x=32
x=32/7
x=4+4/7

See similar equations:

| 6.25t+8=12.5t+3 | | (3/7)*(x+49)+8=35 | | 2(5x-2)^2+5(5x-2)-9=0 | | 3(y–2)+15=–3(y–3)+6y | | 3x-15+x=18+x | | 9m=9+6m | | 7(-x-3)+2=58 | | 1/4z-2=8 | | 5m-18=2(m+5) | | 98=11x-12 | | 2/3+3x/5=31/5 | | -3b=-3b+10 | | 3+3x=129 | | b-(-7)=13 | | (6x+1)+(13x-11)=180 | | 2v-5v+8=-16 | | -8=b-15 | | 9w-34=10(10w-3)-4 | | 7(x+3)+2=58 | | -54=-9m+36 | | 4(3x-15)=-24x | | 15.1+x/6=-4.1 | | 26x=25+22+3X | | 5r+12=r-12 | | 5(x+3)-2(x+4)=28 | | -3+x=4.2 | | m+7m=40-2m | | −5(3x−1)=2(x−68)−29 | | 6w+21=81 | | 6x+27+3+90=180 | | 2v-5v+8=16 | | 0=9j-9j |

Equations solver categories